A kinematic analysis between triple and quadruple revolution figure skating jump - Johnson, M.; King, D. L. (2001)
To increase the revolutions of a toe-loop or a Salchow from a triple to a quadruple, angular velocity must be increased. Decreased moments of inertia permit this to happen. Angular momentum is needed to complete any level of jump; however, the trend shows that it is not increased from the triple to the quadruple. In the Salchow, vertical velocity was also increased from triple to quadruple. This lead to higher jump heights and longer flight times, allowing the extra revolution. A slower approach speed accompanied the greater vertical velocities, as did a different pattern of knee motion during propulsion. This may have allowed the skater to take advantage of eccentric muscle actions in the generation of positive vertical velocity.